Identification of trema in first episode psychosis: a case report - C. Alvarez Garcia; D. García Martínez; L. Nocete Navarro (European Psychiatry, 2022)
Introduction The concept of trema refers to an initial phase in the psychotic process that is characterized by intense anguish, an experience of hostility and a feeling of imminent catastrophe. This situation engenders in the patient a sensation of being in a tunnel than can only lead to something terrible but ineffable.